2003
DOI: 10.1177/0886260503255558
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Link between Child Abuse and Youth Violence

Abstract: This study investigates several factors as possible mediators of physical child abuse in the prediction of violence among adolescents. Prospective and retrospective measures of abuse are compared in mediation tests. Data are from the Lehigh Longitudinal Study, a prospective study of 457 children followed from preschool into adolescence. Structural equation models examined the degree to which abuse is mediated in the prediction of violence through youths' bonds to family, commitment to school, involvement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 35 publications
6
61
1
2
Order By: Relevance
“…Mother's education can be interpreted as a proxy for socioeconomic status (Foshee et al 2005). These results are in line with previous studies regarding the vulnerability related to the low socio-economic level in predicting abuse and in general attitudes about the use of violence (Herrenkohl et al 2003). The relevance of mother's education can reflect an indirect effect being a marker of a low income and poor family, and of a possible maladjusted relationship mother-child that in turn increases the risk for Dating Aggression (Foshee et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Mother's education can be interpreted as a proxy for socioeconomic status (Foshee et al 2005). These results are in line with previous studies regarding the vulnerability related to the low socio-economic level in predicting abuse and in general attitudes about the use of violence (Herrenkohl et al 2003). The relevance of mother's education can reflect an indirect effect being a marker of a low income and poor family, and of a possible maladjusted relationship mother-child that in turn increases the risk for Dating Aggression (Foshee et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…The study found that while both variables were significant predictors, the effect of friend dating violence on the dating behaviours of adolescents was stronger than the effect of inter-parental violence. This finding is consistent with other research that indicates the power of peer influences on behaviour during adolescence (Herrenkohl et al, 2003). This finding has also been shown to be consistent when looking at aggression across gender.…”
Section: The Role Of Peerssupporting
confidence: 82%
“…Others have proposed mediated models of transmission, where the effects of victimization experiences are channeled through cognitive and affective characteristics (Dodge, Bates, & Pettit, 1990). Within these models, victimization experiences are seen as forming the broader context, or representing a non-specific risk domain, that facilitates movement towards a general trajectory of problem behaviors (Herrenkohl, Huang, Tajima, & Whitney, 2003;Loeber & Stouthamer-Loeber, 1986) or serves to impede prosocial development (Tremblay et al, 2004). While the current study is not able to disentangle the exact mechanisms underlying the relationship between victimization and violence, victimization experiences are included as a key domain within models of girls' aggression (Moretti, Odgers, & Jackson, 2004).…”
Section: What Is the Role Of Victimization Experiencesmentioning
confidence: 99%